PENGGUNAAN E-FILING OLEH WAJIB PAJAK DALAM UPAYA MENINGKATKAN KUALITAS PELAYANAN PERPAJAKAN DI KOTA BANDUNG - Ade Irma Hentriwati; Ira Irawati; Candradewini Candradewini (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2018)
Bureaucratic reform in the taxation is begun from the needs of taxpayers to report taxes more quickly, easily, and save on expenses. Responding to the case, the government offers an e-filing facility to the taxpayers in order to report taxes anytime and anywhere. The purpose of this research is to analyze the factors that influence taxpayers to use e-filing, and to measure the level of influence of each variable. This research is important because the use of e-filing by the taxpayers has not been maximized. The sample of this research was 100 respondents, who had an experience in using e-filing. The sampling technique was simple random sampling. Data analysis technique using path analysis. The validity and reliability test of the variables were valid and reliable. The result of the research indicated that the variable of perceived usefulness was not significantly correlated with the variable of behavioral intention (r=0,07), while the variable of perceived ease of use was significantly correlated with the variable of behavioral intention (r=0,33). The variable of service quality was significantly correlated with the variable of user satisfaction (r=0,39). The variable of user satisfaction was significantly correlated with the variable of behavioral intention (r=0,34). The variable of behavioral intention was significantly correlated with the variable of use behavior (r=0,45).